2014
DOI: 10.1136/vr.102303
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antimicrobial susceptibility of Mycoplasma bovis isolates from Great Britain

Abstract: The UK has approximately 10 million cattle (Veterinary Medicines Directorate 2011), and each year approximately 1.9 million of these cattle are affected by respiratory disease. A disease that is often complex, caused by viruses and/or bacteria, with as many as one-third of these infected with the Mycoplasma bovis pathogen (Nicholas and Ayling 2003). The welfare and economic effects of clinical cases of M. bovis on farming are therefore substantial and costs may be even more when morbidity associated with respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 16 publications
1
46
0
1
Order By: Relevance
“…Macrolides have been used traditionally in the therapy of mycoplasmosis in cattle, but now these antibiotics are losing their efficiency against M. bovis in many countries (8,12,14,18). In the present study, the rapid evolution of macrolide and lincomycin resistance was observed in the in vitro-selected M. bovis mutants similarly to avian Mycoplasma species (20), presuming the small number of mutation events needed for the change of antibiotic susceptibility in these cases.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Macrolides have been used traditionally in the therapy of mycoplasmosis in cattle, but now these antibiotics are losing their efficiency against M. bovis in many countries (8,12,14,18). In the present study, the rapid evolution of macrolide and lincomycin resistance was observed in the in vitro-selected M. bovis mutants similarly to avian Mycoplasma species (20), presuming the small number of mutation events needed for the change of antibiotic susceptibility in these cases.…”
Section: Discussionmentioning
confidence: 54%
“…Tetracyclines, and particularly oxytetracycline, are generally used for the treatment of M. bovis-related diseases, but increasing resistance have been reported from Europe and other continents as well (7,14,18). The number of mutations in region Tet-1 was shown to correlate with the increase of MICs to tetracycline in M. bovis strains (13).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Three studies reported highly resistant isolates, with MICs of Ͼ8 g/ml, in the United Kingdom, Japan, and Belgium (9-11), while several others indicated a low to no increase in resistance, except for a few isolates, in Japan, the United States, and several European countries (6,(12)(13)(14)(15). Some of these studies involved isolates collected before 2005 (11, 13), but the majority referred to recent ones (6,9,10,12,14,15), suggesting a recent phenomenon. In the United Kingdom, a shift of resistance from an MIC 90 of 1 g/ml to one of 32 g/ml occurred during the last decade (9, 16).…”
mentioning
confidence: 99%
“…Some of these studies involved isolates collected before 2005 (11,13), but the majority referred to recent ones (6,9,10,12,14,15), suggesting a recent phenomenon. In the United Kingdom, a shift of resistance from an MIC 90 of 1 g/ml to one of 32 g/ml occurred during the last decade (9,16). This significant increase over a relatively short period is indicative of highly efficient resistance mechanisms.…”
mentioning
confidence: 99%